The Existence Of The Tembe Me'e Weaving Tradition As A Representation Of Islamic Values And Local Cultural Identity - Subari Subari; Edi Kurniawan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the existence of the Tembe Me'e Weaving tradition as a representation of Islamic values and the local cultural identity of the Donggo community, Bima Regency. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, in-depth interviews, and documentation. Research informants consisted of traditional leaders, religious leaders, weaving artisans, and Donggo community members who understand the Tembe Me'e Weaving tradition. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions, while data validity was tested using source and method triangulation. The research results show that the Tembe Me'e weaving tradition still exists and plays a significant role in the social life of the Donggo people, particularly in traditional, cultural, and religious activities. This tradition embodies Islamic values such as patience, hard work, simplicity, togetherness, and religiosity. Furthermore, Tembe Me'e is a symbol of local cultural identity, reflecting the character and wisdom of the Donggo people. However, this tradition faces challenges due to modernization, lifestyle changes, and the declining interest of the younger generation in weaving. This study concludes that Tembe Me'e weaving serves not only as a cultural product but also as a representation of Islamic values and the local cultural identity of the Donggo people. Therefore, preservation efforts through cultural education, community empowerment, and support from various parties are needed to ensure this tradition is maintained and passed on to future generations.